Validity of Digital Media Filled with Local Wisdom of Industrial Agriculture in Improving Student’s Self-Regulation and Digital Literacy - Nuraini, Lailatul; Bektiarso, Singgih; Harijanto, Alex; Subiki, Subiki; Maryani, Maryani; Khafidar Rochim, Wildan Jamil; Anggraeni, Nadiah Putri (JURNAL PENDIDIKAN SAINS (JPS), 2023)
This research aimed to analyze aspects of the validity of digital media containing local wisdom of industrial agriculture that has been developed. The research method used is the R and D (Research and Development) research method with the Four-D development model (Define, Design, Develop, Disseminate). At the 4D development stage, in the Develop section, media development and validation activities were carried out by three media and material experts. The data collection technique uses a validation questionnaire. Data analysis technique using descriptive analysis. The validation results for each aspect, namely construct validation of 89.08%, content validation of 90%, Language validation of 86.67%, these three aspects are in the very good category. The results of the overall validation show that digital media based on local wisdom of industrial agriculture achieves a validity score of 88.58% which is in the very good category and is suitable for use. Thus, it can be concluded that digital media containing local wisdom of industrial agriculture can then be used in the process of learning physics in basic physics 1 courses as an alternative solution to innovative learning resources based on local wisdom